Narrative Paradigms: Emotional Intelligence and Strategic Imperatives in HR Professional Designation Preparation - Gifty Parker; Issa Gyimah (International Journal of Management and Data Analytics, 2025)
This study explores the emotional dimensions of HR analytics education among MBA students preparing for the Certified Professional in Human Resources (CPHR) designation. Using qualitative data from faculty narratives at University Canada West (UCW) and insights from prior research, the study examines students’ emotional responses to People Analytics Platforms (PAPs) and the integration of emotional intelligence and cultural competence into HR curricula. Grounded in Bourdieu’s theory of capital, Critical Social Justice Theory, and the Technology Acceptance Model (TAM) extension, the research highlights how emotional intelligence, cultural capital, and social justice considerations shape students’ attitudes toward HR analytics tools. Findings reveal a range of emotional reactions—from curiosity and enthusiasm to frustration and apprehension—underscoring the role of emotional intelligence in managing technological challenges and enhancing decision-making. The integration of the Attitude, Behavior, Knowledge (ABK) model and Emotional Intelligence (EI) Theory further emphasizes emotional awareness and regulation as critical skills for future HR leaders. Practical implications suggest curriculum enhancements that foster emotional competence alongside technical proficiency. The study contributes to HR analytics education by highlighting the interplay between emotional dynamics and technological adoption, offering recommendations for MBA educators to create supportive learning environments. This holistic framework aims to develop students’ analytical capabilities, emotional intelligence, and cultural fluency, equipping them to address the complexities of modern HR practice.